ENGINEERING BEHAVIOUR RICE HUSK ASH BLENDED SOIL AND IT’S POTENTIAL AS ROAD BASE CONSTRUCTION - Agus Setyo Muntohar (Australian Road Research Board, 2003)
The rice husk ash (RHA) is high reactive amorphous silica, which is a suitable raw material for making pozzolanas. The outcomes of this study provide insight into engineering behaviour of open field-burnt rice husk ash mixed expansive soil from Yogyakarta, Indonesia. A series of laboratory tests has been performed subject to engineering properties such as indices properties, bearing of soil and shear strength properties. The experiment confirmed the ashes-lime mixtures diminished moderately the plasticity index of tested soil from 42% to 5% by blending of 6% lime and 13% RHA. Although decrease in dry density, the bearing of soils (California Bearing Ratio) value increases steeply from 3% to 16.3% at a 6% lime - 13% ash mixture. In associate with increase in CBR, the shear strength is also increase. All of these factors can be summarized to say that ashes enhance the engineering properties of lime–treated soils.